Effect of differences in specimen processing and passage technique on recovery of Chlamydia trachomatis. - Jones, R B (J Clin Microbiol, 1989)
We have previously found that optimum recovery of Chlamydia trachomatis in microdilution plate culture required multiple blind passages. However, others have found this not to be the case for culture in vials. In the present study, the effect on recovery of the use of vials (as opposed to microdilution plates) and the effect of vortexing, sonication, or both were compared. Three different passage techniques were also evaluated. Vortexing or sonication resulted in equivalent recoveries. However, compared with vortexing alone, a combination of vortexing and sonication increased recovery from 95 (78%) to 114 (94%) of 121 positive specimens (P = 0.002). In multiple-passage experiments, the combination of vortexing and sonication, compared with vortexing only, increased the proportion of isolates recovered with no more than a single passage from 81 to 96%. Substitution of vials for microdilution plates increased recovery with only a single passage to greater than 96%, irrespective of whether sonication was employed. The most sensitive technique for single-passage technique was one using blunt scraping of cell monolayers with passage of two monolayers to one. The sensitivity of cell culture for C. trachomatis is highly dependent on the technique(s) employed. However, the combination of sonication and vortexing of clinical specimens enhanced recovery in microdilution plates, and a single blind passage did so in both microdilution plates and vials. Consideration should be given to their use for routine clinical cultures.